Attitude stability control system of mobile robot mechanism based on nanosensor. Issue 1 (2nd January 2023) - Song, Dongfang; Ji, Hong; Yin, Guanfei
Abstract : Aiming at the poor stability of attitude control of mobile robot mechanism, a kind of attitude stability control system of mobile robot mechanism based on nanodisplacement sensor is designed. In the hardware part, a hydraulic drive is used to control the action posture of the mobile robot, a nanodisplacement sensor is used to collect the walking data of the robot, and serial communication of the upper computer is used to convert the data into electrical signals to realise the robot posture control. In the software part, the mathematical coordinate system of robot walking is constructed, and the rotating posture of the robot is controlled by the Euler angle. The experimental results show that the control performance of the designed system is stable and the control precision is high, which can realise the attitude stabilisation control of the mobile robot.